YOUTH IDENTITY FROM ECOLOGICAL PERSPECTIVE BETWEEN EDUCATION AND PREVENTION - Nikitorowicz, Jerzy; Sawicki, Krzysztof; Zylkiewicz-Plonska, Emilia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Socialisation is one of the key processes that shapes the identity of youth. This construct, which over the last century has undergone significant transformation, became a pattern for determining the purposes of upbringing (Nature vs. Nurture), or interpretative model that is used to explain character of this process from a socio-cultural perspective. On the basis of ecological framework, the concept of resilience and positive psychology, in recent years it has been developed a new approach towards socialisation - Positive Youth Development (PYD). Because of its relevance, pragmatic assumptions, this model is worth examining in terms of teleology, epistemology and methodical context.According to the Ecological Systems Theory of Urie Bronfenbrenner the youth socialisation process is included in the micro, meso, exo and macro systems. While the socialisation process, youth experiences the interactions between these systems, which in consequence shapes its identity. An element that fits into a methodical context is the characteristic of chosen supportive, educational and preventive actions undertaken towards youth in the northeastern Poland.